JUNIOR HIGH SCHOOL STUDENTS’ ENGAGEMENT IN GAMIFIED LEARNING EXPERIENCES THROUGH QUIZIZZ - Mega Farizia Nur Humairoh; Nur Iqva Hakiki (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Various problems are faced by all academic sectors when studying online during the covid-19 pandemic. Teachers and students feel overloaded with learning at home and accomplishing school during the Covid-19 outbreak, specifically assessment, because the teacher can control and monitor the assessment activity through gamification-based assessment. One gamification-based assessment is Quizizz, created to facilitate online assessment, free user, and easy to apply. This study investigated the students’ perspectives on using Quizizz as students’ assessment tool regarding engagement theory. More specifically, the purposes of this study were to explore students' perspectives in Quizizz as their assessment tool regarding behavioral engagement, emotional engagement, and cognitive engagement. This study was a survey in which the data were collected through a questionnaire about engagement. The research participants were 32 students of secondary schools. The result of this study showed three types of engagement categories considered moderately high interpretation (M. 3.14). Specifically, Students endorsed positive behavioral engagement that demonstrated active participation, contribution, and persistence in using Quizziz. Then, students showed their positive emotions while using Quizziz, including emotional engagement. Also, students viewed good psychological involvement in students’ self-regulation and encouragement in achieving the goal, which indicates a very high interpretation in cognitive engagement. So, Quizizz as a gamification-based assessment could engage students in behavioral, emotional, and cognitive. Thus, it is highly recommended that teachers consider using Quizizz as a good assessment tool to keep students engaged.